The Effectiveness of Discovery and Inquiry Learning Strategies in Improving Students’ Early Math Skills - Rita Mariyana; Myrnawati Crie Handini; Maruf Akbar (JETL (Journal of Education, Teaching and Learning), 2020)
The study aimed to find out the effectiveness of discovery and inquiry learning strategies on the efforts of improving the early math skills of students in kindergartens in West Java Province, Indonesia. This is experimental research. The sampling method was done by multi-stage random sampling with probability sampling and it obtained 72 samples of kindergarten students consisting of 36 children from kindergartens in Bandung, West Java who were treated by discovery learning strategy and 36 children from the kindergartens in West Bandung Regency who was treated using inquiry learning strategy. Data were obtained using a checklist of observation sheets for early math skills of kindergarten children. Data analysis used a quantitative descriptive with a t-test. The findings of the study indicate that discovery-learning strategy is better than inquiry learning strategy in improving early math skills of kindergarten students. It is evidenced by the results showing that the average score of group with discovery learning strategy was 111.63 and the average score of group n using inquiry learning strategy was 101.96 with the result of t-count of 5.551 at the 0.05 level of significance. The conclusion of this research there were differences in early math skills between groups of children with discovery learning strategy and those with the inquiry learning strategy. From the results of data processing and discussion of the study, it was concluded that discovery learning strategy was better than inquiry learning strategy in increasing the score of early math skills of kindergarten children.